Effectiveness of tattoo cream on children’s pain and fear during venipuncture procedure: a randomized controlled trial - Suleman, Sherzad Khudeida; Yahya, Nizer; Nilsson, Stefan; Enskär, Karin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The venipuncture procedure causes significant discomfort, fear, and pain in children. This study aimed to evaluate the effectiveness of TKTX cream, also known as tattoo cream, in reducing pain and fear during venipuncture in children. Methods: In this parallel randomized controlled trial, children aged 6–12 years were randomly assigned to either an intervention group or a control group. The intervention group (n = 44) received TKTX cream during the venipuncture procedure, while the control group (n = 44) received no cream. The outcomes of the procedure were evaluated by the children, their parents, and an observing nurse within 2–3 minutes after the procedure. Results: Patients receiving TKTX cream (5% lidocaine, 5% prilocaine, and 1% epinephrine) reported significantly lower mean levels of pain and fear than did the control group, as measured by the children, mothers, and nurse observers. In the control group, the average pain levels were 6.88, 6.93, and 6.98, whereas in the experimental group, they were significantly lower at 3.02, 3.02, and 2.52, respectively. Furthermore, the TKTX cream group exhibited significantly lower levels of fear than did the control group, at 2.52, 2.57, and 2.52, respectively, compared to 3.02, 3.07, and 3.97, respectively, in the control group. Additionally, TKTX-Cream has been shown to improve the success rate of procedures in children, shorten procedure times, and cause only minor changes to the dermis. Conclusions: This study demonstrated that TKTX-Cream is effective in reducing children’s pain and fear during venipuncture procedures.